Unresolved and Suppressed Scientific Issues Left by the COVID-19 Pandemic - M. V. Supotnitskiy (Вестник войск РХБ защиты)
Highlights- the global response to the COVID-19 pandemic was based on falsified assumptions about vaccines and the suppression of existing knowledge about immunity to coronavirus infections;- global measures against COVID-19, contrary to expectations, were often implemented without accounting for known immunological risks, necessitating a revision of strategies for future pandemics;- russian immunology of dangerous infections, judging by publications from its leading figures, has failed to learn any lessons from the mistakes made during the COVID-19 pandemic. Relevance. The COVID-19 pandemic exposed systemic flaws in infectious disease epidemiology and immunology – issues that were either previously unknown or, more troublingly, deliberately suppressed for non-scientific reasons. Purpose of the study is to identify unresolved and suppressed scientific issues left by the COVID-19 pandemic. Study base sources. Review and problem-focused articles in peer-reviewed English-language scientific journals, accessible via the Internet. Method. Analytical. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed. Over 3,000 scientific publications on the features of the epidemic process, disease immunology, and vaccination complications were identified. Of these, 114 review articles were selected and analyzed. Discussion. Coronavirus infections were well-studied prior to the COVID-19 pandemic. However, during global efforts to combat it, previously accumulated knowledge was disregarded. The investigation into the mechanisms of the epidemic was reduced to political blame-shifting. The origin of the virus remains unknown. Instead of genuine disease immunology, physicians were presented with a surrogate model that falsified the role of antibodies. Immunological phenomena characteristic of coronavirus infections–such as antibody-dependent enhancement (ADE), pathogenic priming, and antigenic imprinting–were deliberately ignored. The toxic and prion-like properties of the spike protein, used as the antigenic component in vector-based mRNA vaccines (Pfizer, Moderna, etc.) and adenoviral vaccines (Oxford–AstraZeneca, Johnson & Johnson, etc.), were concealed from recipients. Under current regulatory frameworks, these products are classified as somatic gene therapy drugs, not vaccines. No scientifically grounded public health measures were developed in advance to counter the pandemic. Conclusions. The pandemic was not only a public health catastrophe but also–more dangerously–a catastrophic collapse of the scientific knowledge applied. This knowledge failed to align with the realities of COVID-19 and will remain inadequate for future pandemics due to an obsessive focus on vaccination, which was justified through falsification, fraud, and violations of laws and constitutional principles. A critical reassessment of the mistakes made during the COVID-19 pandemic is essential, along with the development of a new scientific foundation to address future pandemics and biocrimes.